Reduced C9orf72 protein levels in frontal cortex of amyotrophic lateral sclerosis and frontotemporal degeneration brain with the C9ORF72 hexanucleotide repeat expansion - Waite, Adrian J.; Bäumer, Dirk; East, Simon; Neal, James; Morris, Huw R.; Ansorge, Olaf; Blake, Derek J. (Neurobiology of aging, 2014)
An intronic G4C2 hexanucleotide repeat expansion in C9ORF72 is a major cause of amyotrophic lateral sclerosis and frontotemporal lobar degeneration. Several mechanisms including RNA toxicity, repeat-associated non-AUG translation mediated dipeptide protein aggregates, and haploinsufficiency of C9orf72 have been implicated in the molecular pathogenesis of this disorder. The aims of this study were to compare the use of two different Southern blot probes for detection of repeat expansions in an amyotrophic lateral sclerosis and frontotemporal lobar degeneration pathological cohort and to determine the levels of C9orf72 transcript variants and protein isoforms in patients versus control subjects. Our Southern blot studies identified smaller repeat expansions (250–1800 bp) that were only detectable with the flanking probe highlighting the potential for divergent results using different Southern blotting protocols that could complicate genotype–phenotype correlation studies. Further, we characterize a new C9orf72 antibody and show for the first time decreased C9orf72 protein levels in the frontal cortex from patients with a pathological hexanucleotide repeat expansion. These data suggest that a reduction in C9orf72 protein may be a consequence of the disease.